Analysis of the performances of the 2024 Olympic champion in freestyle wrestling in the category up to 57 kg - Pavlov, Y. E.; Kolodeznikov, K. S.; Uvarov, M. V.; Nikitin, A. S. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to analyze the competitive activity of freestyle wrestler Rei Higuchi.